Aqueous Leaching Prior to Dewatering Improves the Quality of Solid Fuels from Grasslands - Frank Hensgen; Michael Wachendorf (Energies, 2018)
Renewable energies are necessary to reduce greenhouse gas emissions in energy production, and biomass plays a dominant role in the renewable energy sector. Combustion of biomass constitutes an efficient conversion technique, but is hindered by harmful elements which are frequently contained in residual grassland biomass. We investigated the effect of leaching on solid fuel quality with three independent experiments including the following treatments: (1) with or without leaching, (2) with leaching at various water to silage ratios and (3) with the use of press liquid versus fresh water. Biomass was mechanically dehydrated and press cakes for combustion were produced and analyzed for their concentrations of ash, N and minerals harmful for combustion. Solid fuel quality was improved by leaching prior to dewatering, and the application of higher proportions of fresh water enabled even higher quality to be attained.